2000
DOI: 10.1080/109158100225033
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Common Mechanism Approach to the Food Quality Protection Act: Captan and Four Related Fungicides, a Practical Example

Abstract: Under the Food Quality Protection Act (FQPA) of 1996 (Act), the United States Environmental Protection Agency (EPA) is mandated to conduct cumulative risk assessment on pesticides that act through a common mechanism of toxicity. Incumbent on the Agency is the development of sound scientific principles upon which to evaluate compounds for the presence of a common mechanism. Using the currently available draft guidance criteria, this paper employs five fungicides of the same general class, typified by captan, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In CD-1 and B6C3F1 mice, the consistent finding is induction of glandular tumors (adenomas and adenocarcinomas) of the duodenum (Tables 1 and 2 1990; Quest et al�, 1993;Bernard and Gordon, 2000;EFSA, 2009aEFSA, , 2009bGordon, 2010)� The duodenum is the proximal portion of the small intestine� It transitions to the jejunum at the ligament of Treitz� The distal half of the small intestine is referred to as the ileum� In several of the short-and long-term studies involving folpet and related chemicals, some investigators have arbitrarily divided the small intestine into thirds� Regardless of whether the lesions occurred in what was stated as the duodenum or the jejunum, they occurred in the proximal portion of the small intestine, generally near the ampulla of Vater where bile and pancreatic secretions enter the intestine, with high concentrations of bicarbonate raising the pH of the intestinal luminal contents� There has also been an analysis of squamous cell tumors of the nonglandular, forestomach in mice (Figures 3-6)� It is suggested that one possibility is that the large duodenal tumors act Table 1. Tumor incidences of selective tissues in a study in CD-1 mice administered folpet in the diet (Wong, 1985 Table 2.…”
Section: Mousementioning
confidence: 89%
See 4 more Smart Citations
“…In CD-1 and B6C3F1 mice, the consistent finding is induction of glandular tumors (adenomas and adenocarcinomas) of the duodenum (Tables 1 and 2 1990; Quest et al�, 1993;Bernard and Gordon, 2000;EFSA, 2009aEFSA, , 2009bGordon, 2010)� The duodenum is the proximal portion of the small intestine� It transitions to the jejunum at the ligament of Treitz� The distal half of the small intestine is referred to as the ileum� In several of the short-and long-term studies involving folpet and related chemicals, some investigators have arbitrarily divided the small intestine into thirds� Regardless of whether the lesions occurred in what was stated as the duodenum or the jejunum, they occurred in the proximal portion of the small intestine, generally near the ampulla of Vater where bile and pancreatic secretions enter the intestine, with high concentrations of bicarbonate raising the pH of the intestinal luminal contents� There has also been an analysis of squamous cell tumors of the nonglandular, forestomach in mice (Figures 3-6)� It is suggested that one possibility is that the large duodenal tumors act Table 1. Tumor incidences of selective tissues in a study in CD-1 mice administered folpet in the diet (Wong, 1985 Table 2.…”
Section: Mousementioning
confidence: 89%
“…For the duodenal tumors induced in mice by folpet, the mode of action involves irritation-related cytotoxicity with consequent cellular regeneration ultimately leading to the development of tumors� The critical key event involves consumption of sufficiently high levels of folpet that yield a cytotoxic concentration of folpet and its degradation product, thiophosgene� Combined, these chemicals can cause cytotoxicity in the duodenum (Table 6)� In the stomach and duodenum there is cytotoxicity from the direct reaction of folpet with cellular components containing thiol groups as well as from the highly reactive thiophosgene, a hydrolysis product of folpet, which reacts with thiols as well as other cellular constituents (see Figures 1 and 2)� Folpet itself, like captan (Wilkinson et al�, 2004), is reactive with thiol groups, which generates thiophosgene (Figure 1)� However, thiophosgene is also reactive with thiol groups (Figure 2), with a half-life of less than 1 s (0�6 s in human blood)� Thiophosgene, thus, is generated either by the reaction of folpet with thiol groups or following hydrolysis of folpet� Direct interaction of folpet with thiol groups is the primary source of the thiophosgene� The hydrolysis of folpet to thiophosgene is highly pH dependent� The reaction occurs readily at neutral to alkaline pH but significantly less at low pH� Because of their marked reactivity, folpet and thiophosgene will react rapidly with thiol groups and not reach DNA or DNA-related targets (e�g�, histones) Liu and Fishbein, 1967;Lukens, 1966;Lukens et al�, 1965;Siegel, 1971aSiegel, , 1971bBernard and Gordon, 2000)� This is highlighted by a pair of key in vivo studies that show folpet and captan do not induce genotoxicity, as evidenced by the lack of increased nuclear aberrations in the tumor target site, the duodenum (Chidiac and Goldberg, 1987;Gudi and Krsmanovic, 2001)� Thus, DNA damage is highly unlikely and not detected in studies designed to assess this effect at the target tissue in vivo (Arce et al�, 2010)�…”
Section: Key Eventsmentioning
confidence: 99%
See 3 more Smart Citations